2017
DOI: 10.1093/ajh/hpx139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the National Essential Public Health Services Policy on Hypertension Control in China

Abstract: The National EPHS program improved the treatment and control among hypertension patients. Expanding its program reach could further benefit the cardiovascular health of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 27 publications
3
67
0
1
Order By: Relevance
“…An average of ¥15 was allotted per capita in 2009 and was increased to ¥55 in 2018. Following the previous literature, findings of the studies showed the following: the coverage of BPHS has increased greatly, but it has not reached the goal of universal coverage,22 23 especially coverage of migrants24 25; the utilisation of the BPHS is generally improved, but some of the services are underutilised26 27; ensuring equal access to the basic public health services is improved,28 29 and the gaps between urban–rural areas and different regions have been narrowed, but inequality still exists24 30 31; and with respect to the effects of the BPHS policy, there are some improvements in maternal health services and reductions in maternal mortality,32 and improved the treatment and control among patients with hypertension and type 2 diabetes 33 34. New evidence from the Global Burden of Disease Study showed that China has made substantial progress in reducing the burden of many diseases and disabilities 35…”
Section: Coverage Of Health Servicesmentioning
confidence: 99%
“…An average of ¥15 was allotted per capita in 2009 and was increased to ¥55 in 2018. Following the previous literature, findings of the studies showed the following: the coverage of BPHS has increased greatly, but it has not reached the goal of universal coverage,22 23 especially coverage of migrants24 25; the utilisation of the BPHS is generally improved, but some of the services are underutilised26 27; ensuring equal access to the basic public health services is improved,28 29 and the gaps between urban–rural areas and different regions have been narrowed, but inequality still exists24 30 31; and with respect to the effects of the BPHS policy, there are some improvements in maternal health services and reductions in maternal mortality,32 and improved the treatment and control among patients with hypertension and type 2 diabetes 33 34. New evidence from the Global Burden of Disease Study showed that China has made substantial progress in reducing the burden of many diseases and disabilities 35…”
Section: Coverage Of Health Servicesmentioning
confidence: 99%
“…In 2009, the Chinese government implemented the Essential Public Health Services (EPHS), a national health service program promoting the management of NCDS represented by hypertension and diabetes in primary care [5]. The hypertension service for EPHS focuses on follow-up and management for hypertension patients and developing primary prevention of related education on knowledge and behavior for all residents [6]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, based on the situation in Sichuan, improvements of the following five aspects may be effective. Firstly, we can rely on National Essential Public Health Services (EPHS), which can improve the treatment and control on patients, as well as basic healthcare services to every citizen [43,44].…”
Section: Discussionmentioning
confidence: 99%